2021
DOI: 10.26858/ijole.v5i1.19625
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and challenges of Trainee Translators Participating in Translation Training

Abstract: The research on translation has been found very little particularly within the Indonesian context. This study aims to explore the motivation of students participating in translation training. This case study with an action learning model recruits 40 student participants. They involve in the research voluntarily and provide very insightful reflection at the end of the training session. The key to the findings is that students portray their future selves as the key motivational factor in participating in transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Findings showed that most fan translators think of themselves as consumer producers and show traits similar to those of their readers. Jabu and Abduh (2021) explored the motivation of 40 students participating in translation training in the Indonesian context. Findings showed that students portray their future selves as the key motivational factor in participating in translation courses.…”
Section: Literature Review Motivation In Second Language Learningmentioning
confidence: 99%
“…Findings showed that most fan translators think of themselves as consumer producers and show traits similar to those of their readers. Jabu and Abduh (2021) explored the motivation of 40 students participating in translation training in the Indonesian context. Findings showed that students portray their future selves as the key motivational factor in participating in translation courses.…”
Section: Literature Review Motivation In Second Language Learningmentioning
confidence: 99%
“…The problem is that the translation of literary work like novels is still very limited due to some factors and one of them is we have lack of awareness of the richness of our own culture [1] that our art as in our culture cannot be exposed as we expect it. This becomes complicated as the rareness of the translation work leads to the rareness of research on translation itself [2]. ICADECS Apart from the situation, the research about translation of Indonesian art as a part of non-equivalence word [3,4,5], and as a part of cultural items [6,7] has been located.…”
Section: Introductionmentioning
confidence: 99%
“…Translation is profitable language proficiency for communication and professional practice. Translation nowadays has attracted great attention due to the demands of educational and industrial circles (Jabu, et al, 2021;Pourfarhad, et al, 2018). Translation contributes to the absorption of science and technology especially for non-English speaking countries (Siregar, 2017).…”
Section: Introductionmentioning
confidence: 99%